Inflammasomes in Tissue Damages and Immune Disorders After Trauma - Bortolotti, Perrine; Faure, Emmanuel; Kipnis, Eric (Frontiers in Immunology, 2018)
Trauma remains a leading cause of death worldwide. Hemorrhagic shock and direct injury to vital organs are responsible for early mortality whereas most delayed deaths are secondary to complex pathophysiological processes. These processes result from imbalanced systemic reactions to the multiple aggressions associated with trauma. Trauma results in the uncontrolled local and systemic release of endogenous mediators acting as danger signals (damage-associated molecular patterns; DAMPs). Their recognition by the innate immune system triggers pro-inflammatory immune response paradoxically associated with concomitant immunosuppression. These responses, ranging in intensity from inappropriate to overwhelming, promote the propagation of injuries to remote organs, leading to multiple organ failure and death. Some of the numerous DAMPs released after trauma trigger the assembly of intracellular multiprotein complexes named inflammasomes. Once activated by a ligand, inflammasomes lead to the activation of a caspase. Activated caspases allow the release of mature forms of interleukin-1β and interleukin-18 and trigger a specific pro-inflammatory cell death termed pyroptosis. Accumulating data suggest that inflammasomes, mainly NLRP3, NLRP1 and AIM2, are involved in the generation of tissue damage and immune dysfunction after trauma. Following trauma-induced DAMP(s) recognition, inflammasomes participate in multiple ways in the development of exaggerated systemic and organ-specific inflammatory response, contributing to organ damage. Inflammasomes are involved in the innate responses to traumatic brain injury and contribute to the development of acute respiratory distress syndrome. Inflammasomes may also play a role in post-trauma immunosuppression mediated by dysregulated monocyte functions. Characterizing the involvement of inflammasomes in the pathogenesis of post-trauma syndrome is a key issue as they may be potential adjuvant therapeutic targets. This review summarizes the current knowledge on the roles of inflammasomes in trauma